Chickpea flour supplemented high protein composite formulation for flatbreads: Effect of packaging materials and storage temperature on the ready mix. (March 2017) - Pathania, Shivani; Kaur, Amarjeet; Sachdev, Poonam A.
Highlights: Two ready mix formulations for preparation of flat bread locally known as missi roti were developed. Seasonal ingredients were dried and powdered for incorporation into the formulation. Formulations packed in zip pouches, aluminum pouches and HDPE at room and refrigerated temperatures for tested for quality attributes. Formulations stored in aluminum pouches at refrigeration temperature were the best, however, all the samples were good till four months of storage. Abstract: Shelf life studies are gaining impetus due to the consumer's attentiveness towards excellence of the packaged products. The present study was carried out to develop a composite premix formulation for chickpea supplemented flatbread and to estimate the suitability of packaging material and storage temperature on its quality. Whole wheat flour was supplemented with chickpea flour from 10 to 50%; fenugreek powder and onion flakes at 0–20%; salt, ginger powder, green chilli powder and red chilli powder at 0–2%, mango powder at 0–5%; glycerol mono stearate (GMS) and sodium steaoryl-2-lactylate (SSL) at 0–0.50% and fat at 0–4%. Two formulations (I and II) were prepared after selecting the appropriate levels of ingredients by sensory evaluation using trial and error method. Formulations were packed in zip pouch, aluminum laminate and high density poly ethylene at room and refrigeration temperatures. Changes in the total composition, water activity, free fatty acid, overall acceptability and texture of flatbreads were assessed for four months. Storage period had most significant effect followed by storage temperature and packaging material on quality attributes of formulations. All the samples were in acceptable condition where aluminum laminate and refrigerated temperature were the best combination for storage of formulation I and II.